LONG-TERM FSO/FPSO CHARTER RATE ESTIMATION - Kurniawati, Hesty A; Aryawan, Wasis D; Baidowi, Achmad (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2016)
Most of the charter rate data provided in the market is for the short-term and it is based on freight rate for cargo ships. This paper offers a method to estimate long-term charter rate for special ships such as FSO and other supporting vessels. The method is utilizing engineering economy such as IRR and goal seek facility provided in spreadsheet. The IRR is iterated 2% above the basic saving interest rate to find more attractive charter rate and the sensitivity analysis provides flexibility for the owner in order to anticipate the volatility of economic condition